Seasonal Mixing and Biological Controls of the Carbonate System in a River-Dominated Continental Shelf Subject to Eutrophication and Hypoxia in the Northern Gulf of Mexico - Huang, Wei-Jen; Cai, Wei-Jun; Hu, Xinping (Frontiers in Marine Science, 2021)
Large rivers export a large amount of dissolved inorganic carbon (DIC) and nutrients to continental shelves; and subsequent river-to-sea mixing, eutrophication, and seasonal hypoxia (dissolved oxygen < 2 mg⋅L–1) can further modify DIC and nutrient distributions and fluxes. However, quantitative studies of seasonal carbonate variations on shelves are still insufficient. We collected total alkalinity (TA), DIC, and NO3– data from nine cruises conducted between 2006 and 2010 on the northern Gulf of Mexico continental shelf, an area strongly influenced by the Mississippi and Atchafalaya Rivers. We applied a three-end-member model (based on salinity and potential alkalinity) to our data to remove the contribution of physical mixing to DIC and nitrate distribution patterns and to derive the net in situ removal of DIC and nitrate (ΔDIC and ΔNO3–, respectively). Systematic analyses demonstrated that the seasonal net DIC removal in the near-surface water was strong during summer and weak in winter. The peak in net DIC production in the near-bottom, subsurface waters of the inner and middle sections of the shelf occurred between July and September; it was coupled, but with a time lag, to the peak in the net DIC removal that occurred in the near-surface waters in June. A similar 2-month delay (i.e., January vs. November) could also be observed between their minima. A detailed examination of the relationship between ΔDIC and ΔNO3– demonstrates that net biological activity was the dominant factor of DIC removal and addition. Other effects, such as air–sea CO2 gas exchange, wetland exports, CaCO3 precipitation, and a regional variation of the Redfield ratio, were relatively minor. We suggest that the delayed coupling between eutrophic surface and hypoxic bottom waters reported here may also be seen in the carbon and nutrient cycles of other nutrient-rich, river-dominated ocean margins worldwide.